Normalised insurance losses from Australian natural disasters: 1966–2017. (20th October 2019) - McAneney, John; Sandercock, Benjamin; Crompton, Ryan; Mortlock, Thomas; Musulin, Rade; Pielke, Roger; Gissing, Andrew
ABSTRACT: The paper updates normalisation of the Insurance Council of Australia's Disaster List in the light of debate about the contribution of global warming to the rising cost of natural disasters. Normalisation estimates losses from historical events in a common year, here 'season' 2017 defined as the 12-month period from 1 July 2017. The number and nominal cost of new residential dwellings are key normalising factors and post-1974 improvements in construction standards in tropical cyclone-prone parts of the country are explicitly allowed for. 94% of the normalised losses arise from weather-related perils – bushfires, tropical cyclones, floods and severe storms – with the 1999 Sydney hailstorm the most costly single event (AUD5.6 billion). When aggregated by season, there is no trend in normalised losses from weather-related perils; in other words, after we normalise for changes we know to have taken place, no residual signal remains to be explained by changes in the occurrence of extreme weather events, regardless of cause. In sum, the rising cost of natural disasters is being driven by where and how we chose to live and with more people living in vulnerable locations with more to lose, natural disasters remain an important problem irrespective of a warming climate.